Single-bundle ACL reconstruction with and without extra-articular reconstruction: evaluation with robotic lower leg rotation testing and patient satisfaction scores - Branch, Thomas (Knee Surg Sports Traumatol Arthrosc, 2015)
PURPOSE: The purpose of this study was to compare the biomechanical characteristics and patient outcomes after either isolated intraarticular ACL reconstruction or intraarticular reconstruction with lateral extra-articular tenodesis. In addition, we aimed to evaluate biomechanical parameters of the entire uninjured, contralateral knee as a baseline during the analysis. METHODS: Eighteen patients were evaluated at an average of 9.3 years after ACL reconstruction. Twelve patients had an intraarticular reconstruction (BTB), and six had an additional lateral extraarticular procedure (BTB/EAR). Patients were selected for the additional procedure by the operating surgeon based on clinical and radiological criteria. At the time of review, each patient was assessed using subjective patient questionnaires, manual laxity testing, and instrumented laxity testing. Each knee was also evaluated using a robotic lower leg axial rotation testing system. This system measured maximum internal and external rotations at 5.65 Nm of applied torque and generated load deformation curves and compliance data. Pointwise statistical comparisons within each group and between groups were performed using the appropriate paired or unpaired t test. Features were extracted from each load deformation curve for comparative analysis. RESULTS: There were no significant differences between the two groups with respect to the patient satisfaction scores or to laxity testing (manual or instrumented). Robotic testing results for within-group comparisons demonstrated a significant reduction in maximum external rotation (8.77°) in the reconstructed leg when compared to the healthy leg (p < 0.05) in the BTB/EAR group, with a non-significant change in internal rotation. The slope of the curve at maximum internal rotation was also significantly greater in the reconstructed legs for the BTB/EAR group (p < 0.05), indicating reduced endpoint compliance or a harder endpoint. Finally, the leg that received the extra-articular tenodesis had a trend towards a reduced total leg axial rotation. Conversely, patients in the BTB group demonstrated no significant differences between their legs. For between-group comparisons, there was a significant increase in maximum internal rotation in the healthy legs in the BTB/EAR group compared with the healthy legs in the BTB group (p < 0.05). If the injured/reconstructed legs were compared, the significant difference at maximum internal rotation disappeared (p < 0.10). Similarly, the healthy legs in patients in the BTB/EAR group had a significantly more compliant or softer endpoint in internal rotation, greater maximum internal rotation, and more internal rotation at torque 0 in their healthy legs compared with the healthy legs in the BTB group (p < 0.05). These same differences were not noted in the reconstructed knees. The only identifiable significant difference between the injured/reconstructed legs was rotation at 0 torque (p < 0.05). CONCLUSIONS: In this group of patients who were at an average of 9 years from surgery, the addition of a lateral extra-articular reconstruction to a standard bone–tendon–bone intraarticular ACL reconstruction does reduces internal rotation of the tibia with respect to the femur when compared to intraarticular reconstruction alone. It appears that the selection process for inclusion into the BTB/EAR group included an increase in total axial rotation of the healthy knee during the examination along with a decrease in endpoint stiffness at maximum internal rotation. LEVEL OF EVIDENCE: II.